X-RAY OUTPUT DOSE ASSESSMENT OF SOME X-RAY FACILITIES IN JOS PLATEAU STATE - khan, Aasik (IPHO-Journal of Advance Research in Games and Sports, 2024)
The use of x-ray machines in both private and governmenthospitals in Jos Plateau state are on the increase.Adequate quality control measures of such equipment are of particular importance to prevent unwanted radiation exposure and to ensure dose optimization. In this study, the dose reproducibility, exposure linearity and coefficient of variation of five x-ray units were investigated using a well calibrated Unfors Mult-o-meter 710l. The results indicatedthat of the five P1, P2, P3, P4 and P5 x-ray machines studied, 80% (P2, P3,P4andP5) had tolerable dose reproducibility,100%(P1, P2, P3, P4 and P5) exposure linearity and 80% (P2,P3, P4 and P5) coefficient of variation. 80% of all the studied x-ray units had acceptable deviation with tolerance limit of5%. The study, therefore concluded that monitoring of the performance characteristics of the x-ray equipment will enhance quality practice and radiation safety for patients and staff and should be carried out at least annually and when major parts are replaced or fixed.